“Production Process Innovation to Increase Business Competitiveness in the Future case study PT Panca Setia Makmur” - Muslikun (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2025)
In facing increasingly competitive market dynamics, innovation in the production process is a key factor in maintaining and increasing business competitiveness. This case study discusses PT Panca Setia Makmur's efforts to develop production process innovation through the application of new technology, optimizing work flow, and improving product quality. This research uses a qualitative approach with observation methods and in-depth interviews with management and related employees. The results show that planned and integrated innovation not only increases production efficiency, but also expands market opportunities and strengthens the company's position amidst industrial competition. This study provides strategic recommendations for other companies wishing to build competitive advantage through sustainable innovation in the production sector